Proof [large type] - Michaels, Fern (Michaels, Fern. Lost and found, 2024)
"While Cullen Bodman focuses on their family's antiques restoration business, his sister Luna's next-door Namaste Café brings in new clientele. As a thank you to his sister, Cullen retrieves Luna's childhood dresser from storage and refinishes it. A delighted Luna rummages through the drawers and discovers mementos of her friend Brendan. But a flurry of emails leads to a very brief death notice: Born. Died. Nothing else. Beyond Luna's sadness is her uncanny intuition that something is off, a feeling that intensifies when she glimpses a person who seems to be Brendan. Is her old friend really alive? And if so, who faked his death, and why?"--